2021
DOI: 10.3389/fnins.2021.691931
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Ameliorates Chronic Inflammatory Pain-Related Anxiety by Activating PV Interneurons in the Anterior Cingulate Cortex

Abstract: Chronic inflammatory pain is a common clinical disease that tends to be associated with negative emotions such as anxiety and depression. The anterior cingulate cortex (ACC) is involved in pain and pain-related anxiety, and γ-aminobutyric acid (GABA)-ergic interneurons play an important role in chronic pain and anxiety. Electroacupuncture (EA) has good analgesic and antianxiety effect, but the underlying mechanisms have not yet been fully elucidated. In this study, we established a chronic inflammatory pain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…The subtypes of GABAergic neurons mainly include parvalbumin (PV), somatostatin (SST), vasoactive intestinal peptide (VIP), and neuropeptide Y (NPY) [26]. Our previous paper has been observed that only PV interneurons were involved in chronic inflammatory pain related anxiety-like behaviors and pain sensation [27]. We observed the expression of PV positive cells and its coexpression with c-Fos.…”
Section: Reduction Of Inhibitory Presynaptic Transmission In the Acc ...mentioning
confidence: 78%
“…The subtypes of GABAergic neurons mainly include parvalbumin (PV), somatostatin (SST), vasoactive intestinal peptide (VIP), and neuropeptide Y (NPY) [26]. Our previous paper has been observed that only PV interneurons were involved in chronic inflammatory pain related anxiety-like behaviors and pain sensation [27]. We observed the expression of PV positive cells and its coexpression with c-Fos.…”
Section: Reduction Of Inhibitory Presynaptic Transmission In the Acc ...mentioning
confidence: 78%
“…As a common analgesic method worldwide, EA affects multiple targets and acts on multiple levels, and EA has been widely used in the clinic and has been shown to achieve good clinical effects [ 40 42 ]. Accumulated evidence has found that EA can alleviate the abnormal pain sensation and negative emotions induced by chronic pain in rats [ 26 , 27 , 43 ]. We previously reported the analgesic and antidepressant effects of EA at different frequencies [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture (EA) is effective for relieving pain and emotional diseases [ 26 , 27 ]. Moreover, it is widely used in China and all over the world because it is safer, more effective, and has fewer side effects than other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that SNI induces PV loss and AIS length reduction in the infralimbic cortex [ 62 ]; however, whether SNI causes such structural plasticity in the ACC has remained unclear. Pharmacological or chemogenetic activation of PV-INs, but not SOM-INs, in the ACC was revealed to alleviate mechanical allodynia and anxiety-like behavior in rats with chronic inflammatory pain [ 63 , 64 , 65 ]. PV-IR neurons in the human ACC comprise dendritic and axonal processes, and there are two dense PV-immunolabeled neuropil bands in ACC layers III and V [ 66 ].…”
Section: Discussionmentioning
confidence: 99%